Diagnostic Analysis of Junior High School Students' Mathematical Critical Thinking Ability in Solving Problems of Numbers with Powers and Root Forms - Pertiwi, Budi Wahyu; Jaelani, Anton (Desimal: Jurnal Matematika, 2026)
Mathematical critical thinking is increasingly recognized as a core competence for enabling students to interpret problems, evaluate procedures, justify conclusions, and make reasoned mathematical decisions. Yet, students’ difficulties in exponents and radicals often reflect not only procedural inaccuracy but also fragmented reasoning that remains insufficiently diagnosed in classroom-based mathematics assessment. This study aimed to diagnose junior high school students’ mathematical critical thinking ability in solving exponent and radical problems through three indicators: elementary clarification, inference, and strategies and tactics. A descriptive diagnostic mixed-method design was employed involving 23 Grade IX students at SMP Negeri Satu Atap 1 Cimanggu, Indonesia. Data were collected using essay-based mathematical critical thinking tasks and analyzed through descriptive statistics and qualitative interpretation of students’ written responses. The quantitative findings revealed a critically low level of mathematical critical thinking, with a mean score of 26.57, a standard deviation of 3.55, the highest score of 35, and the lowest score of 20. None of the students reached the very good, good, or moderate categories; 26.09% were classified as low, while 73.91% were classified as very low. Qualitative analysis showed that students could identify limited explicit information but struggled to evaluate solution completeness, construct evidence-based inferences, justify strategy efficiency, and interpret results contextually. These findings indicate that students’ weaknesses are structural within the reasoning process rather than merely computational. The study contributes a diagnostic perspective by shifting the analysis from achievement-based classification toward indicator-based mapping of mathematical reasoning weaknesses, offering a foundation for more reflective, conceptually grounded, and reasoning-oriented mathematics instruction.